Repairing the damage: The effect of price expectations on auto-repair price quotes - Meghan R. Busse; Ayelet Israeli; Florian Zettelmeyer (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2013)
In this paper we investigate whether sellers treat consumers differently on the basis of how well-informed consumers appear to be. We implement a large-scale field experiment in which callers request price quotes from automotive repair shops. We show that sellers alter their initial price quotes depending on whether consumers appear to be well-informed, uninformed, or poorly informed about market prices. We find that repair shops quote higher prices to callers who cite a higher expected price. We find that women are quoted higher prices than men when callers signal that they are uninformed about market prices. However, gender differences disappear when callers mention an expected price for the repair. Finally, we find that repair shops are more likely to offer a price concession if asked to do so by a woman than a man.
Keywords: 330